A Novel Orbit Parameterization in Spherical Coordinates - Kevin J. Napier; Matthew J. Holman (The Planetary Science Journal)
We present a novel orbit parameterization in spherical coordinates. This parameterization enables the mixing of varying and invariant orbital parameters, and clarifies the physics of the orbit. It also simplifies the process of placing synthetic populations at exactly specified locations on the sky, which is particularly useful for survey design and simulation studies.